Effect of salicylic acid and gibberellin on yield and yield components of Mungbean (Vigna radiata) - Mojtaba Keikha; Mohsen Noori; Abbas Keshtehgar (پژوهش‌های حبوبات ایران)
Introduction The plant hormones such as salicylic acid and gibberellin can affect the quantity and quality of crops. External application of plant growth regulators as a strategy for improving salt tolerance in plants is discussed. Foreign Salicylic acid can regulate antioxidant enzyme activity and increase plant resistance to abiotic stresses. Salicylic acid reduction due to ethylene through the effect on the mechanisms of enzymatic and non-enzymatic of plant improves oxidative stress protection. Gibberellic acid increased amylase activity in the cotyledons of mung bean seedlings. Gibberellin are for the elongation of cells in the embryo and endosperm during seed germination.